Produção de cana-energia e suas características energéticas em condição tropical - Sarmento, Pedro Luã Vieira de Souza (2019)
The oxcessive use of inputs such as oil and coal in recent decades has caused an imbalance in climate conditions on the planet, mainly due to the high release of greenhouse gases, and the imbalance has led to a rise in global temperature. As a strategy to meet the global demand for decarbonization of the atmosphere and supply the world's energy demand, we mention the cultivation of biomass with high capacity to generate energy and among them the sugarcane. The present work aimed to determine the production components for energy cane and their energy characteristics for conversion of biomass to energy. An experimental study consisting of 7 energy cane genotypes and one sugar cane genotype was conducted. The experimental design was in randomized blocks with three replications. The intercepted photosynthetically active radiation was calculated taking into account the leaf area index, the incident photosynthetically active radiation and the light extinction coefficient (k). The higher calorific value, fuel content and ash content were determined every two months. The energy conversion efficiency was calculated by the relationship between the energy present in the biomass throughout the cycle and the intercepted photosynthetic irradiation, active photosynthetic irradiation and global canopy irradiation. The coefficient of extinction of light was on average 0.88 for cane-energy and 0.75 for sugarcane. The efficiency in the use of radiation was 1.77 g MJ-1 for RB92579 and 2.28 g MJ-1, on average for sugarcane genotypes.The calorific value for the sugarcane genotypes at harvest was, on average, 18,716 J g-1, and 18,318 J g-1 for RB92579. RB92579 had the lowest ash content at harvest (2.4%) and the highest combustibility content (97.6%), than the sugarcane genotypes. Despite the lower highest combustibility, the sugarcane genotypes were more efficient in the conversion of intercepted photosynthetic energy and consequently produced more energy per unit area. The RB92579 variety produced 535 GJ ha-1 of energy and the average of the sugarcane genotypes was 830 GJ ha-1.